2003
DOI: 10.1097/00005373-200301000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Chitosan-Based Hemostatic Dressing on Blood Loss and Survival in a Model of Severe Venous Hemorrhage and Hepatic Injury in Swine

Abstract: A chitosan dressing reduced hemorrhage and improved survival after severe liver injury in swine. Further studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
179
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(182 citation statements)
references
References 39 publications
3
179
0
Order By: Relevance
“…A large effect size was determined for this experiment based upon previous work by Alam and Pusateri [21,27]. Using G-Power 3.00, an effect size of 0.6, a power of 0.80, and an a of 0.05, it was determined that a sample size of five swine per group was needed for this study.…”
Section: Resultsmentioning
confidence: 99%
“…A large effect size was determined for this experiment based upon previous work by Alam and Pusateri [21,27]. Using G-Power 3.00, an effect size of 0.6, a power of 0.80, and an a of 0.05, it was determined that a sample size of five swine per group was needed for this study.…”
Section: Resultsmentioning
confidence: 99%
“…An earlier chitosanbased dressing has also been previously shown to be effective in an alternate model of hepatic trauma in nonheparinised swine. 10 The addition of a significant amount of heparin to this model makes it more challenging, but more useful given that patients who have had major liver trauma are liable to be coagulopathic. In spite of this, haemostasis was usually achieved, supporting both the in vitro laboratory evidence where clotting occurs in fully anti-coagulated blood and our own previous experience.…”
Section: Discussionmentioning
confidence: 99%
“…8 The deployment of chitosan-based products in the military setting is supported by in vivo experimental work showing 100% effectiveness in an industry standard model of lethal groin haemorrhage in swine, 9 and improved outcome in a model of hepatic injury in swine. 10 We have previously shown that Omni-Stat ® (MedTrade Products Ltd, Electra House, Electra Way, Crewe Business Park, Crewe CW1 6GL, UK), a proprietary preparation of chitosan granules, has the ability to provide reliable haemostasis in a moderately heparinised modification of an industry standard model of femoral artery haemorrhage (manuscript submitted). We are also aware of anecdotal reports of successful haemostasis using chitosan granules and gauzes in the management of hepatic injuries in the current conflict in Afghanistan.…”
mentioning
confidence: 99%
“…[1][2][3][4] In the case of cardiac surgery, for example, bleeding may result from several aspects inherent to cardiac procedures, including the placement of cardiac suture lines in great vessels or chambers of the heart, as well as the creation of high-pressure anastomoses. 5 Therefore, effective and rapid hemostasis is critical to optimize surgical outcomes.…”
Section: Introductionmentioning
confidence: 99%